Polyphenol-rich oolong tea alleviates obesity and modulates gut microbiota in high-fat diet-fed mice - Li, Ang; Wang, Jin; Kou, Ruixin; Chen, Mengshan; Zhang, Bowei; Zhang, Yan; Liu, Jingmin; Xing, Xiaolong; Peng, Bo; Wang, Shuo (Frontiers in Nutrition, 2022)
Obesity is a major public health issue worldwide. Oolong tea (OT), which is partially fermented from camellia sinensis leaves, has proven health benefits and potential preventive applications in multiple studies. However, research on the role of OT in obesity prevention and potential mechanisms is still limited. The purpose of this study was to investigate the modulatory effects of OT intervention on high-fat diet (HFD)-induced-obesity and gut microbiota dysbiosis using an obese mouse model. Our results showed that 8-week OT supplementation with 93.94% polyphenols significantly decreased body weight gain, adipose tissue mass, together with the serum levels of triglyceride (2.60 mmol/L), cholesterol (5.49 mmol/L), and low-density lipoprotein cholesterol (0.61 mmol/L) in HFD-fed mice. Meanwhile, OT intervention was observed to improve fat accumulation, hepatic damage, glucose intolerance, endotoxemia and alleviate inflammation by decreasing the levels of pro-inflammatory factors. OT also upregulated expression of genes including Srebf1, Ppara, Lxra, Pgc1a and Hsl, and downregulated expression of genes including Leptin, Il-6 and Il-1b. In addition, the gut dysbiosis characterized by decreased flora diversity and increased Firmicutes/Bacteroidetes ratio in obese mice were recovered by OT intervention. Certain differentially abundant microbes caused by HFD feeding, including Enterococcus, Intesinimonas, Blautia, and Bilophila were also improved by OT treatment. This study demonstrated that OT, as a novel resource of dietary polyphenols, exhibited a protective effect on HFD-induced obesity and gut microbiota disorder.